Oil agent for ultra-high molecular weight polyethylene fiber and preparation method thereof

By using SiO2-CNTs composite materials as antistatic agents, combined with smoothing agents, emulsifiers and stabilizers, an oil agent for ultra-high molecular weight polyethylene fibers is formed, which solves the problem of insufficient heat resistance and antistatic properties of the fiber, and achieves efficient thermal stability and antistatic properties improvement, which is suitable for high-temperature environments and simplifies the process flow.

CN119102013BActive Publication Date: 2025-03-04JIANGSU NEW HORIZON ADVANCED FUNCTIONAL FIBER INNOVATION CENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411586303.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-04
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

In practical applications, ultra-high molecular weight polyethylene fibers have problems such as poor heat resistance and poor antistatic properties. The prior art is difficult to improve their heat resistance and antistatic properties at the same time. The process is cumbersome and costly, and the fibers after treatment are poor in antistatic properties and uniformity.

Method used

SiO2-CNTs composite material is used as an antistatic agent, combined with smoothing agent, emulsifier and stabilizer to form an oil agent for ultra-high molecular weight polyethylene fibers. The composite material is modified with a silane coupling agent and coated with polyaniline, and is loaded on a silica carrier. The formed oil agent can form a protective film on the surface of the fiber, improving thermal stability and reducing electrostatic accumulation.

Benefits of technology

It realizes effective reduction of static problems without affecting the basic physical properties of the fiber, improves the thermal stability and anti-static properties of the fiber, is suitable for high-temperature environments, and simplifies the process flow and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119102013B_ABST
    Figure CN119102013B_ABST
Patent Text Reader

Abstract

The present invention relates to an oil for ultra-high molecular weight polyethylene fiber and a preparation method thereof, which belongs to the technical field of fiber oils, and solves the problem of insufficient antistatic and heat resistance of ultra-high molecular weight polyethylene fibers in the prior art. The present invention provides an oil for ultra-high molecular weight polyethylene fibers, the oil comprising a smoothing agent, an emulsifier, an antistatic agent and a stabilizer; the anti-stabilizer is a SiO2-CNTs composite material. The oil simultaneously achieves a significant improvement in the heat resistance and antistatic properties of the fiber, and compared with the prior art practice of adding an antistatic agent alone, the antistatic agent is more evenly dispersed and has a better antistatic effect. The static voltage of the fiber treated with the oil is ≤0.041 kV, the initial modulus is ≥1900 cN / dtex, the initial breaking strength is ≥40.0 cN / dtex, and the breaking strength decreases less under high temperature conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fiber oil agents, and in particular to an oil agent for ultra-high molecular weight polyethylene fibers and a preparation method thereof. Background Art

[0002] Ultra-high molecular weight polyethylene (UHMWPE) fibers have been widely used in many fields due to their excellent mechanical properties, such as bulletproof vests, cut-resistant gloves, ropes, fishing nets, and medical devices. UHMWPE fibers have extremely high strength, excellent wear resistance, low friction coefficient, and good impact resistance. However, this fiber also has some significant disadvantages in practical applications, mainly including poor heat resistance and poor antistatic properties.

[0003] UHMWPE fiber has a low melting point of about 130°C, which is much lower than the melting point of other high-performance fibers (such as aramid fibers). In high-temperature environments, UHMWPE fibers are prone to deformation and degradation, resulting in a significant decrease in their mechanical properties. For example, in industrial high-temperature environment applications, the heat resistance of the material directly affects its service life and safety. In addition, the heat treatment processes involved in the textile processing, such as heat setting and ironing, will also have an adverse effect on UHMWPE fibers, limiting their application in these fields.

[0004] UHMWPE fiber has poor antistatic performance, which is mainly due to its extremely low conductivity, which makes it easy to accumulate static electricity during use. The accumulation of static electricity not only affects the processing performance of the fiber, such as easily absorbing dust and impurities during spinning, weaving and finishing, resulting in a decline in product quality; at the same time, in certain specific environments, such as flammable and explosive environments, the accumulation of static electricity may cause fire or explosion, posing a serious safety hazard.

[0005] At present, there are some modification methods and treatment technologies on the market to address the problems of poor heat resistance and antistatic performance of UHMWPE fibers. For example, by coating the fiber surface with high temperature resistant materials to improve its heat resistance, or adding antistatic agents to improve its antistatic performance. However, on the one hand, these technologies cannot simultaneously improve heat resistance and antistatic performance, and on the other hand, the antistatic performance and uniformity of the treated fibers are poor, and the treatment process is cumbersome and costly, which cannot meet the needs of actual production. Summary of the invention

[0006] In view of the above analysis, the embodiments of the present invention aim to provide an oil agent for ultra-high molecular weight polyethylene fibers and a preparation method thereof, so as to solve at least one of the problems that the existing ultra-high molecular weight polyethylene fibers have insufficient antistatic and heat resistance, the existing technology cannot simultaneously improve the antistatic and heat resistance of ultra-high molecular weight polyethylene fibers and has complicated processes and high costs, and the antistatic performance and uniformity of the treated fibers are poor.

[0007] The invention provides an oil agent for ultra-high molecular weight polyethylene fiber, which comprises a smoothing agent, an emulsifier, an antistatic agent and a stabilizer; the antistatic agent is a SiO2-CNTs composite material.

[0008] Specifically, the components of the oil agent are as follows by mass: 50 to 70 parts of a smoothing agent, 50 to 60 parts of an emulsifier, 4 to 8 parts of an antistatic agent, and 1 to 2 parts of a stabilizer.

[0009] Specifically, the preparation method of the SiO2-CNTs composite material is:

[0010] Firstly, the carbon nanotubes are modified by using a silane coupling agent, then the modified carbon nanotubes are coated by using polyaniline, and finally the modified carbon nanotubes coated with polyaniline are loaded on a silicon dioxide carrier to obtain a finished SiO2-CNTs composite material, namely the antistatic agent.

[0011] Specifically, the lubricant is one or more of lauryl oleate, isooctyl oleate, isooctyl stearate, triolein, and mineral oil.

[0012] Specifically, the emulsifier is one or more of cardanol polyoxyethylene ether, polyglycerol monofatty acid ester, and castor oil polyoxyethylene ether.

[0013] Specifically, the stabilizer is one or more of acrylic acid polyether silicone oil, Tween 80, polyether modified silicone oil, and trifluoropropyl methyl silicone oil.

[0014] Specifically, the ultra-high molecular weight polyethylene fiber treated with the oil has an electrostatic voltage of ≤0.041 kV, an initial modulus of ≥1900 cN / dtex, an initial breaking strength of ≥40.0 cN / dtex, and the fiber is placed in a 200° C. oven for 72 hours and then taken out, and the breaking strength decreases by ≤9.2%.

[0015] The present invention also discloses a method for preparing the oil, which is characterized by comprising the following specific steps:

[0016] S21: weigh the raw materials according to the preset formula, put the smoothing agent and the emulsifier into a stirring tank, and stir them evenly at room temperature;

[0017] S22: While continuing to stir, slowly add the antistatic agent to ensure that the antistatic agent is evenly dispersed throughout the mixture;

[0018] S23: Add stabilizer to the mixture and continue stirring for more than 30 minutes to ensure that all ingredients are fully blended to obtain a semi-finished oil preparation;

[0019] S24: adjusting the pH value and viscosity of the semi-finished oil, filtering and filling into a storage container, i.e., the finished oil.

[0020] Specifically, the pH value ranges from 6 to 7, and the viscosity ranges from 100 mPa·s to 115 mPa·s; the pH regulator used is potassium hydroxide or triethanolamine.

[0021] The present invention also discloses a method for using the oil, comprising the following specific steps:

[0022] S31: preparing an ultra-high molecular weight polyethylene high viscosity solution;

[0023] S32: Extruding the high viscosity solution through a spinning nozzle with a spinneret aperture of 1 mm and an aspect ratio of 6 to 12 to form filaments at a spinning temperature of 250° C. to 280° C. to obtain ultra-high molecular weight polyethylene fibers;

[0024] S33: After the initial cooling, the fiber is immediately sent to the stretching machine for heat stretching; the stretching temperature is set at 120℃~140℃, and the stretching ratio is 5~10 times of the original length;

[0025] S34: The stretched fiber is oiled by a coating device, cooled and dried after oiling, and then rolled up on a reel to obtain a finished fiber product.

[0026] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0027] 1. The present invention adopts a new type of SiO2-CNTs composite material as an antistatic agent, and combines it with a smoothing agent, an emulsifier, and a stabilizer to form an oil agent for ultra-high molecular weight polyethylene fibers with excellent performance. The oil agent can form a protective film on the fiber surface, improve the thermal stability of the fiber, and effectively reduce the static electricity accumulation on the fiber surface by adding an antistatic agent.

[0028] The SiO2-CNTs composite material is prepared by the following method: firstly, carbon nanotubes are modified by a silane coupling agent, then the modified carbon nanotubes are coated with polyaniline, and finally the polyaniline-coated modified carbon nanotubes are loaded on a silica carrier to obtain a finished SiO2-CNTs composite material, namely the antistatic agent.

[0029] Compared with existing antistatic agents, the antistatic agent has better thermal and electrical conductivity, and has good affinity with other components of the oil agent, and can be evenly dispersed in the oil agent; moreover, the antistatic agent has good high temperature resistance, avoiding failure during use in high temperature scenes, so that the antistatic performance of the treated fiber is still excellent at high temperatures.

[0030] As the main matrix of antistatic agent, carbon nanotube has good thermal and electrical conductivity, so it can be used as a good thermal conductive and antistatic material. However, due to its unique carbon structure, the surface of carbon nanotube is mainly hydrophobic, which makes them poorly dispersible in oil (organic solvent). The present invention uses silane coupling agent to modify it, and the siloxane group can form a covalent bond with the functional group (such as carboxyl, hydroxyl, etc.) on the surface of carbon nanotube through condensation reaction, so as to be anchored on the surface of carbon nanotube. By introducing flexible chain segments to provide sufficient steric hindrance, direct contact between carbon nanotubes and the effect of van der Waals force are avoided. The modified carbon nanotubes are not easy to aggregate or re-aggregate, making it easier to interact with organic molecules in the oil, thereby improving the dispersibility of carbon nanotubes in the oil.

[0031] Compared with other polymers, polyaniline has good electrical conductivity. Both polyaniline and carbon nanotubes are rich in π electron systems. The continuous electron transport network formed by π-π stacking interaction can effectively improve the overall electrical conductivity of the material. Carbon nanotubes provide fast electron transport channels, and the conductivity of polyaniline further enhances these channels. This enhanced electron transport ability allows charges to be quickly conducted on the surface or in the body of the material, thereby effectively dissipating static electricity accumulation and reducing the generation and accumulation of static electricity. Furthermore, through π-π interactions, the polyaniline molecular chain forms a uniform and continuous coating on the surface of carbon nanotubes, which can act as a physical barrier to prevent the oxidation of carbon nanotubes during processing or application.

[0032] Silica has excellent thermal stability and can maintain its physical and chemical properties unchanged in high temperature environments, thus providing a stable base for the entire composite material. By introducing polyaniline-coated carbon nanotubes supported by silica carriers in the spinning oil, the thermal stability of the fiber during processing and application can be increased, especially in environments that need to withstand high temperature processing or operation, to avoid the loss or decomposition of antistatic agents under high temperature conditions and thus failure. On the other hand, the surface roughness and pore structure of silica particles also help to physically embed or attach carbon nanotubes, reducing the sedimentation or aggregation of carbon nanotubes in the oil. Ensure that the processing quality and performance of each batch of fibers are consistent. This improved dispersibility helps the continuity and uniformity of the fiber during the production process and reduces the incidence of breakage and defects.

[0033] The ultra-high molecular weight polyethylene fiber treated with the oil containing the antistatic agent has an electrostatic voltage of ≤0.041 kV, an initial modulus of ≥1900 cN / dtex, an initial breaking strength of ≥40.0 cN / dtex, and a small decrease in breaking strength under high temperature conditions.

[0034] 2. By making a reasonable component ratio, better oil performance can be obtained. Preferably, the components of the oil are calculated by mass as follows: 50-70 parts of smoothing agent, 50-60 parts of emulsifier, 4-8 parts of antistatic agent, and 1-2 parts of stabilizer.

[0035] 3. The preparation method and use method of the oil agent are simple, can be prepared based on existing equipment, and have a simple process and low cost. It can simultaneously improve the heat resistance and antistatic properties of ultra-high molecular weight polyethylene fibers, and is suitable for large-scale production and large-scale promotion.

[0036] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The accompanying drawings are only used for the purpose of illustrating specific embodiments and are not to be considered as limiting the present invention. In the entire drawings, the same reference symbols represent the same components;

[0038] Figure 1 This is a photo of the oil for ultra-high molecular weight polyethylene fiber in Example 1;

[0039] Figure 2 Flow chart for the preparation of antistatic agent. DETAILED DESCRIPTION

[0040] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0041] The invention provides an oil agent for ultra-high molecular weight polyethylene fiber, which comprises a smoothing agent, an emulsifier, an antistatic agent and a stabilizer; the antistatic agent is a SiO2-CNTs composite material.

[0042] Specifically, the oil agent is suitable for ultra-high molecular weight polyethylene fiber, including a smoothing agent, an emulsifier, an antistatic agent and a stabilizer; by weight, the smoothing agent is 50 to 70 parts, the emulsifier is 50 to 60 parts, the antistatic agent is 4 to 8 parts, and the stabilizer is 1 to 2 parts.

[0043] The role and content of each component are determined as follows:

[0044] Smoothing agent: Smoothing agent can reduce the friction coefficient of fibers in spinning, stretching, stretching, spinning and weaving processes, improve the strength of the oil film, and thus protect the fibers. Too little amount of smoothing agent will lead to insufficient lubricity on the fiber surface, which is easy to break during processing; too much amount may cause the fiber surface to be too smooth, affecting the bonding force between fibers. Experimental verification shows that when the amount of smoothing agent is 50-70 parts, the comprehensive performance of the oil agent is better.

[0045] Emulsifier: By reducing the interfacial tension between the oil and water phases, the two immiscible liquids form a stable emulsion (i.e., ensure the uniformity of the oil). Too little emulsifier will cause uneven distribution of the oil on the fiber surface, affecting the lubrication effect; too much may increase costs and may affect the mechanical properties of the fiber. Experimental verification shows that when the emulsifier is 50 to 60 parts, the comprehensive performance of the oil is better.

[0046] Antistatic agent: Too little antistatic agent cannot effectively reduce static electricity accumulation; too much antistatic agent may affect the mechanical properties and feel of the fiber. Experimental verification shows that when the antistatic agent is 4 to 8 parts, the overall performance of the oil is better.

[0047] Stabilizer: Stabilizer can improve the stability, high temperature resistance, sun resistance, storage resistance and dispersibility of the oil during high-speed processing. Too little stabilizer will cause the oil to fail during high temperature or long-term use, and too much will affect the oiling effect and comprehensive performance of the oil. Experimental verification shows that when the stabilizer is 1 to 2 parts, the comprehensive performance of the oil is better.

[0048] Synergistic effect: The use of antistatic agents in combination with smoothing agents and emulsifiers can effectively reduce static electricity problems without affecting the basic physical properties of the fiber, allowing the fiber to maintain good fluidity and handling properties during high-speed processing.

[0049] When the smoothing agent and the emulsifier are used in a proper proportion, an oil with both good lubricity and excellent dispersibility can be formed, which helps to provide a continuous and uniform lubricating protective layer in the spinning, weaving and other processes, reducing the risk of broken wires and fiber damage.

[0050] Specifically, the preparation method of the SiO2-CNTs composite material is:

[0051] Firstly, the carbon nanotubes are modified by using a silane coupling agent, then the modified carbon nanotubes are coated by using polyaniline, and finally the modified carbon nanotubes coated with polyaniline are loaded on a silicon dioxide carrier to obtain a finished SiO2-CNTs composite material, namely the antistatic agent.

[0052] The present invention adopts carbon nanotubes as the main matrix of the antistatic agent. Carbon nanotubes have good thermal and electrical conductivity, so they can be used as good thermal and antistatic materials. However, due to their unique carbon structure, the surface of carbon nanotubes is mainly hydrophobic, which makes them less dispersible in oils (organic solvents). The present invention uses silane coupling agents to modify them. The siloxane groups can form covalent bonds with functional groups (such as carboxyl, hydroxyl, etc.) on the surface of carbon nanotubes through condensation reactions, thereby anchoring on the surface of carbon nanotubes. By introducing flexible segments to provide sufficient steric hindrance, direct contact between carbon nanotubes and the effect of van der Waals forces are avoided. The modified carbon nanotubes are not easy to aggregate or re-aggregate, making it easier to interact with organic molecules in the oil, thereby improving the dispersibility of carbon nanotubes in the oil.

[0053] Compared with other polymers, polyaniline has good electrical conductivity. Both polyaniline and carbon nanotubes are rich in π electron systems. The continuous electron transport network formed by π-π stacking interaction can effectively improve the overall electrical conductivity of the material. Carbon nanotubes provide fast electron transport channels, and the conductivity of polyaniline further enhances these channels. This enhanced electron transport ability allows charges to be quickly conducted on the surface or in the body of the material, thereby effectively dissipating static electricity accumulation and reducing the generation and accumulation of static electricity. Furthermore, through π-π interactions, the polyaniline molecular chain forms a uniform and continuous coating on the surface of carbon nanotubes, which can act as a physical barrier to prevent the oxidation of carbon nanotubes during processing or application.

[0054] Silica has excellent thermal stability and can maintain its physical and chemical properties unchanged in high temperature environments, thus providing a stable base for the entire composite material. By introducing polyaniline-coated carbon nanotubes supported by silica carriers in the spinning oil, the thermal stability of the fiber during processing and application can be increased, especially in environments that need to withstand high temperature processing or operation, to avoid the loss or decomposition of antistatic agents under high temperature conditions and thus failure. On the other hand, the surface roughness and pore structure of silica particles also help to physically embed or attach carbon nanotubes, reducing the sedimentation or aggregation of carbon nanotubes in the oil. Ensure that the processing quality and performance of each batch of fibers are consistent. This improved dispersibility helps the continuity and uniformity of the fiber during the production process and reduces the incidence of breakage and defects.

[0055] The specific steps include:

[0056] S1: weighing or measuring carbon nanotubes and ethanol, adding the carbon nanotubes into the ethanol and performing ultrasonic dispersion to obtain a carbon nanotube solution;

[0057] S2: taking a quantity of silane coupling agent and dissolving it in ethanol, slowly adding distilled water under stirring conditions, adjusting the pH value, and allowing the mixed solution to stand until the silane coupling agent is fully hydrolyzed to obtain a silane coupling agent solution;

[0058] S3: slowly adding the carbon nanotube solution into the silane coupling agent solution and stirring, and obtaining a reaction mixture after the reaction is completed;

[0059] S4: baking the reaction mixture, cooling it to room temperature and then vacuum drying it to obtain carbon nanotubes modified with a silane coupling agent;

[0060] S5: ultrasonically dispersing the carbon nanotubes modified with the silane coupling agent in an aqueous solution and adding aniline, stirring and mixing the mixture thoroughly; cooling the mixture in an ice bath and adding an ammonium persulfate solution, stirring the mixture at 0°C, and after the reaction is completed, filtering, washing and drying the mixture to obtain the polyaniline-coated carbon nanotubes;

[0061] S6: adding the polyaniline-coated carbon nanotubes to an aqueous solution containing sodium dodecylbenzene sulfonate, and subjecting the solution to ultrasonic treatment to obtain a carbon nanotube suspension; slowly adding silicon dioxide powder to the carbon nanotube suspension, stirring evenly, and heating and continuing to stir to obtain a composite semi-finished product;

[0062] S7: drying and heat treating the semi-finished composite material, and after cooling, screening and washing to obtain a finished SiO2-CNTs composite material, namely the antistatic agent.

[0063] Specifically, the main purpose of step S1 is to pre-treat the carbon nanotubes by adding the carbon nanotubes into ethanol and ultrasonically dispersing them for more than 30 minutes using an ultrasonic processor, which can effectively remove impurities and aggregates on the surface of the carbon nanotubes.

[0064] Specifically, in step S1, the mass ratio of carbon nanotubes to ethanol is 1:100-120. If too much carbon nanotubes are added, the impurity removal effect is poor; if too little carbon nanotubes are added, the preparation / production efficiency is reduced.

[0065] Specifically, in step S2, the volume ratio of the silane coupling agent to ethanol is 1:10-12; the volume ratio of the silane coupling agent to distilled water is 1:3-3.5; the pH value adjustment interval is 4-5, and the standing time is ≥2h; the silane coupling agent is KH-550 or KH-560. The hydrolysis reaction of the silane coupling agent (such as KH-550 or KH-560) in water is significantly affected by the pH value. Under neutral or slightly acidic conditions, the hydrolysis rate of these coupling agents is moderate, which is conducive to controlling the progress of the reaction and the quality of the product. If the pH value is too high (alkaline), the silane coupling agent may hydrolyze too quickly, resulting in unstable products; if the pH value is too low (too acidic), the hydrolysis of the coupling agent may be inhibited, affecting the final reaction effect. The pH value in the range of 4 to 5 helps the silane groups on the silane coupling agent to react more effectively with the functional groups (such as carboxyl, hydroxyl, etc.) on the surface of the carbon nanotubes. This coupling effect can improve the interfacial compatibility and make the modified carbon nanotubes better dispersed in the final composite material. At the specified pH value and standing time (at least 2 hours), preferably 2 to 6 hours, it can ensure that the silane coupling agent is fully hydrolyzed without excessive polymerization, which is beneficial to subsequent processing and application. Sufficient hydrolysis is the prerequisite for ensuring that the coupling agent can effectively act on carbon nanotubes and other matrix materials.

[0066] Specifically, the pH regulator used is potassium hydroxide or triethanolamine.

[0067] Specifically, in step S3, the mass ratio of the silane coupling agent solution to the carbon nanotube solution is 0.2 to 0.4:1, and the stirring time is ≥4 hours to ensure sufficient contact and reaction between the carbon nanotubes and the coupling agent. The siloxane group can form a covalent bond with the functional groups (such as carboxyl and hydroxyl) on the surface of the carbon nanotube through a condensation reaction, thereby anchoring on the surface of the carbon nanotube. By introducing a flexible segment to provide sufficient steric hindrance, direct contact between the carbon nanotubes and the action of van der Waals forces are avoided. The modified carbon nanotubes are not easy to aggregate or re-aggregate, making it easier to interact with the organic molecules in the oil, thereby improving the dispersibility of the carbon nanotubes in the oil.

[0068] Specifically, the specific operation of step S4 is: transferring the reaction mixture to a constant temperature oven and keeping it at 80-100° C. for 12-14 hours; after cooling to room temperature, drying the reaction mixture in a vacuum drying oven for 24-30 hours to obtain carbon nanotubes modified with a silane coupling agent.

[0069] Specifically, in step S5, the mass ratio of carbon nanotubes modified with silane coupling agent to aniline is 1:6-100, and a magnetic stirrer is used to stir at room temperature to ensure that aniline and carbon nanotubes modified with silane coupling agent are fully mixed. Here, water is only used as a solvent or dispersion matrix, and will be removed later by drying and other steps. Therefore, the amount of water added can ensure its dispersion effect. The specific amount can be adjusted according to actual conditions and should not be too much or too little. The mixed solution is placed in an ice bath to cool, and a pre-dissolved ammonium persulfate solution is slowly added to start the polymerization reaction. The mass ratio of ammonium persulfate (here refers to the solute mass) to aniline is 0.05-0.1:1, the reaction time is 4-6 hours, and the reaction temperature is 0°C (ice bath).

[0070] The mass ratio of carbon nanotubes modified with silane coupling agent to aniline (1:6-100) is to ensure the full use of aniline so that it can undergo uniform polymerization reaction on the surface of carbon nanotubes. The carbon nanotubes serve as the core, and aniline polymerizes on their surface to form a polyaniline wrapping layer. If too much aniline is added, unreacted aniline may remain, which will affect the electrical properties and thermal stability of the composite material; if too little is added, it may not be enough to completely cover the carbon nanotubes, resulting in decreased conductivity and mechanical properties.

[0071] The mass ratio of ammonium persulfate to aniline is (0.05-0.1:1). As an initiator, the amount of ammonium persulfate should be appropriate to control the polymerization reaction rate and degree of polymerization of aniline. This ratio is to ensure the controllability of the reaction and the uniformity of the product. Too much ammonium persulfate may cause the polymerization reaction to be too fast, affecting the growth of the polyaniline chain and making the polyaniline distribution uneven; too little may lead to incomplete polymerization and reduce the performance of the product.

[0072] Controlling the reaction temperature (0°C) and conducting the reaction in an ice bath can greatly control the polymerization rate and slow down the reaction, thereby facilitating a more uniform polyaniline coating. The 0°C environment helps reduce side reactions and undesirable polymerization pathways. In a 0°C ice bath environment, the formation of polyaniline is a free radical polymerization reaction initiated by the initiator ammonium persulfate. Aniline molecules are first oxidized by ammonium persulfate to form free radicals, which then connect to form polyaniline chains. Low temperatures help control the reaction rate, reduce chain breaks and nonspecific reactions, and thus obtain a more uniform polyaniline layer.

[0073] Specifically, the solid and the liquid are separated by filtration, and the precipitate is washed with a large amount of distilled water to remove unreacted monomers and by-products; the washed carbon nanotubes (process state) are transferred to a vacuum drying oven and dried at 60-80° C. for not less than 24 hours to obtain polyaniline-coated carbon nanotubes.

[0074] It is worth noting that polyaniline has good electrical conductivity compared to other polymers, and both polyaniline and carbon nanotubes are rich in π electron systems. The continuous electron transport network formed by π-π stacking interactions can effectively improve the overall electrical conductivity of the material. Carbon nanotubes provide fast electron transport channels, and the conductivity of polyaniline further enhances these channels. This enhanced electron transport capability allows charges to be quickly conducted on the surface or in the body of the material, thereby effectively dissipating static electricity accumulation and reducing the generation and accumulation of static electricity. Furthermore, through π-π interactions, the polyaniline molecular chains form a uniform and continuous coating on the surface of carbon nanotubes, which can act as a physical barrier to prevent the oxidation of carbon nanotubes during processing or application.

[0075] Specifically, in step S6, the mass concentration of the sodium dodecylbenzene sulfonate aqueous solution is 1-1.2%, the volume ratio of the polyaniline-coated carbon nanotubes to the sodium dodecylbenzene sulfonate aqueous solution is 1:400-500, and the ultrasonic treatment time is ≥1h to obtain a well-dispersed carbon nanotube suspension; the mass ratio of the silicon dioxide powder to the polyaniline-coated carbon nanotubes is 8-15:1, the heating temperature is 80°C-100°C, and the reaction time is ≥3 hours, so that the silicon dioxide and the carbon nanotubes are more closely combined.

[0076] It is worth noting that silica has excellent thermal stability and can maintain its physical and chemical properties unchanged in high temperature environments, thus providing a stable base for the entire composite material. By introducing polyaniline-coated carbon nanotubes supported by silica carriers in spinning oils, the thermal stability of the fibers in processing and applications can be increased, especially in environments that require high temperature processing or operation. On the other hand, the surface roughness and pore structure of silica particles also help to physically embed or attach carbon nanotubes, reducing the sedimentation or aggregation of carbon nanotubes in the oil. Ensure that the processing quality and performance of each batch of fibers are consistent. This improved dispersibility helps the continuity and uniformity of the fibers during the production process and reduces the incidence of breakage and defects.

[0077] Specifically, in step S7, the semi-finished composite material product is dried in air.

[0078] Specifically, the specific operation of the heat treatment in step S7 is to dry the semi-finished composite material in air, and then heat it to 500±100°C in a tube furnace at a heating rate of 5±1°C / min, and the treatment time is 120 to 160min. Heat treatment can promote the physical and chemical bonding between different components in the composite material. For example, between polyaniline-coated carbon nanotubes and silicon dioxide, heat treatment can promote better bonding between silicon dioxide, carbon nanotubes and polyaniline, and enhance the overall structural stability of the composite material. Secondly, through the heating process, residual solvents and moisture in the composite material can be removed, further improving the thermal stability of the material. This is particularly important for materials used in high temperature environments, and can ensure that their performance in practical applications will not be reduced by high temperature. For composite materials containing conductive polymers (such as polyaniline) and carbon nanotubes, heat treatment can help form a more continuous and uniform conductive network and improve the overall conductivity of the material.

[0079] After cooling, the unreacted materials were removed through conventional screening and washing processes to obtain the final SiO2-CNTs composite material.

[0080] Furthermore, the lubricant is one or more of lauryl oleate, isooctyl oleate, isooctyl stearate, triolein, and mineral oil. The above substances have good lubricity, can increase the softness of the fiber, and have excellent lubricity and stability, can effectively reduce the friction between the fibers, and have certain anti-oxidation properties.

[0081] Furthermore, the emulsifier is one or more of cardanol polyoxyethylene ether, polyglycerol monofatty acid ester, and castor oil polyoxyethylene ether. The above substances have good emulsifying properties and chemical stability, are non-irritating to fibers, and have a certain lubricating effect.

[0082] Furthermore, the stabilizer is one or more of acrylic acid polyether silicone oil, Tween 80, polyether modified silicone oil, and trifluoropropyl methyl silicone oil. These stabilizers have high chemical stability and can maintain their structure unchanged under various processing and use conditions, thereby ensuring the long-term effectiveness of the oil performance; these stabilizers can improve the lubricity and dispersibility of the oil, ensuring the smoothness and uniform coating of the fiber during the processing; these stabilizers can show good stability under different temperature and environmental conditions, especially in high-temperature and high-speed industrial applications, which helps to protect the performance of the fiber during processing and use.

[0083] Specifically, the ultra-high molecular weight polyethylene fiber treated with the oil has an electrostatic voltage of ≤0.041 kV, an initial modulus of ≥1900 cN / dtex, an initial breaking strength of ≥40.0 cN / dtex, and the fiber is placed in a 200° C. oven for 72 hours and then taken out, and the breaking strength decreases by ≤9.2%.

[0084] The present invention also discloses a method for preparing the oil, which is characterized by comprising the following specific steps:

[0085] S21: weigh the raw materials according to the preset formula, put the smoothing agent and the emulsifier into a stirring tank, and stir them evenly at room temperature;

[0086] S22: While continuing to stir, slowly add the antistatic agent to ensure that the antistatic agent is evenly dispersed throughout the mixture;

[0087] S23: Add stabilizer to the mixture and continue stirring for more than 30 minutes to ensure that all ingredients are fully blended to obtain a semi-finished oil preparation;

[0088] S24: adjusting the pH value and viscosity of the semi-finished oil, filtering and filling into a storage container, i.e., the finished oil.

[0089] Specifically, the pH value ranges from 6 to 7, and the viscosity ranges from 100 mPa·s to 115 mPa·s; the pH regulator used is potassium hydroxide or triethanolamine.

[0090] Specifically, the viscosity of the mixture can be adjusted by adding a proper amount of distilled water or a suitable diluent (one or more of ethanol, acetone and water).

[0091] The present invention also discloses a method for using the oil, comprising the following specific steps:

[0092] S31: preparing an ultra-high molecular weight polyethylene high viscosity solution;

[0093] S32: Extruding the high viscosity solution through a spinning nozzle with a spinneret aperture of 1 mm and an aspect ratio of 6 to 12 to form filaments at a spinning temperature of 250° C. to 280° C. to obtain ultra-high molecular weight polyethylene fibers;

[0094] S33: After the initial cooling, the fiber is immediately sent to the stretching machine for heat stretching; the stretching temperature is set at 120℃~140℃, and the stretching ratio is 5~10 times of the original length;

[0095] S34: The stretched fiber is oiled by a coating device, cooled and dried after oiling, and then rolled up on a reel to obtain a finished fiber product.

[0096] Exemplarily, a high-viscosity solution of ultra-high molecular weight polyethylene can be obtained by the following method: mixing UHMWPE powder with a solvent (one or more of p-xylene / decalin, tetralin, kerosene, liquid paraffin, and white oil) in a heated and stirred container, and fully heating to 130° C. to 160° C. to completely dissolve it to form a high-viscosity solution; the mass content of ultra-high molecular weight polyethylene is 15 to 18%.

[0097] Specifically, the coating equipment in step S34 is a dipping tank or a spray system, and the oiling speed is 20m / min to 30m / min to ensure that the fibers are evenly coated with the oiling agent.

[0098] Specifically, the cooling in step S34 can be air cooling or water bath cooling, and the cooling time is 10 to 20 seconds to stabilize the coating of the oil on the fiber surface.

[0099] Furthermore, generally speaking, the fiber product specification after winding is 5 to 10 kg / roll.

[0100] Source of raw materials for testing:

[0101] Ultra-high molecular weight polyethylene was purchased from Zhejiang Jiuding Chemical Materials Co., Ltd., brand: U-PE350-II, molecular weight of 3500000-8000000 g / mol, bulk density of 0.30-0.50 g / cm 3 .

[0102] Multi-walled carbon nanotubes were purchased from Xianfeng Nano, model number XFM22, with a purity of 95%, a length of 0.5 μm to 2 μm, and a diameter of 20 nm to 30 nm.

[0103] Silica was purchased from Aijiexu Chemical Technology (Shanghai) Co., Ltd. with an average particle size of 5-10 μm and a surface area of ​​800 m 2 / g, pore volume is 3cm 3 / g.

[0104] Aniline was purchased from Tokyo Chemical Industry Co., Ltd.

[0105] Example 1

[0106] Preparation of antistatic agent:

[0107] S1: weighing or measuring 1 part of carbon nanotubes and 100 parts of ethanol by weight, adding the carbon nanotubes into the ethanol and performing ultrasonic dispersion to obtain a carbon nanotube solution;

[0108] S2: According to the volume ratio, 1 part of KH-550 was measured and dissolved in 10 parts of ethanol, and 3 parts of distilled water were slowly added under stirring, and the pH value was adjusted to 4. The mixed solution was allowed to stand for 3 hours until the silane coupling agent was fully hydrolyzed to obtain a silane coupling agent solution;

[0109] S3: slowly adding the carbon nanotube solution into the silane coupling agent solution and stirring for 4 hours, and obtaining a reaction mixture after the reaction is completed; the mass ratio of the silane coupling agent to the carbon nanotube is 0.2:1.

[0110] S4: baking the reaction mixture, cooling it to room temperature and then vacuum drying it to obtain carbon nanotubes modified with a silane coupling agent.

[0111] S5: Ultrasonic dispersion of carbon nanotubes modified with silane coupling agent in aqueous solution and adding aniline, stirring and mixing thoroughly; ice-cooling and adding ammonium persulfate solution, stirring is continued at 0°C for 5 hours, and after the reaction is completed, polyaniline-coated carbon nanotubes are obtained by filtering, washing and drying; the mass ratio of carbon nanotubes modified with silane coupling agent to aniline is 1:6, and aniline:ammonium persulfate = 1:0.05.

[0112] S6: Adding polyaniline-coated carbon nanotubes into an aqueous solution containing 1 wt.% of sodium dodecylbenzene sulfonate at a mass ratio of 1:400, and obtaining a carbon nanotube suspension after ultrasonic treatment; slowly adding silica powder into the carbon nanotube suspension, stirring evenly, heating to 90°C and continuing stirring for 3 hours to obtain a composite material semi-finished product; the mass ratio of silica to polyaniline-coated carbon nanotubes is 8:1.

[0113] S7: Dry the semi-finished composite material in air, and then heat it to 500±100°C in a tubular furnace at a heating rate of 5±1°C / min for 120 to 160 min. After cooling, the semi-finished composite material is sieved and washed to obtain a finished SiO2-CNTs composite material, i.e., the antistatic agent.

[0114] Oil configuration:

[0115] The preset formula is: by mass, 50 parts of lauryl oleate as a lubricant, 50 parts of cardanol polyoxyethylene ether as an emulsifier, 5 parts of an antistatic agent, and 1 part of acrylic acid polyether silicone oil as a stabilizer.

[0116] S21: weigh the raw materials according to the preset formula, put the smoothing agent and emulsifier into a stirring tank, and stir them evenly at room temperature at a stirring speed of 900 r / min;

[0117] S22: While continuing to stir, slowly add the antistatic agent to ensure that the antistatic agent is evenly dispersed throughout the mixture;

[0118] S23: Add stabilizer to the mixture and continue stirring for more than 30 minutes to ensure that all ingredients are fully blended to obtain a semi-finished oil preparation;

[0119] S24: The pH value of the semi-finished oil is adjusted to 6 and the viscosity is adjusted to 110 mPa·s, and the semi-finished oil is filtered and filled into a storage container, i.e., the finished oil.

[0120] Oiling process:

[0121] S31: preparing an ultra-high molecular weight polyethylene high viscosity solution;

[0122] The ultra-high molecular weight polyethylene high viscosity solution can be obtained by the following method: UHMWPE powder and white oil are mixed in a heated and stirred container, and fully heated to 130°C to completely dissolve them to form a high viscosity solution; the content of ultra-high molecular weight polyethylene is 15 wt.%.

[0123] S32: extruding the high viscosity solution through a spinning nozzle with a spinneret aperture of 1 mm and an aspect ratio of 6 to form filaments at a spinning temperature of 250° C. to obtain ultra-high molecular weight polyethylene fibers;

[0124] S33: After the initial cooling, the fiber is immediately sent to the stretching machine for thermal stretching; the stretching temperature is set at 120°C and the stretching ratio is 5 times the original length;

[0125] S34: The stretched fiber is oiled through a coating device at an oiling speed of 20 m / min. After oiling, the fiber is cooled and dried, and then rolled up on a reel to obtain a finished fiber product.

[0126] Example 2

[0127] Preparation of antistatic agent:

[0128] S1: weighing or measuring 1 part of carbon nanotubes and 120 parts of ethanol by weight, adding the carbon nanotubes into the ethanol and performing ultrasonic dispersion to obtain a carbon nanotube solution;

[0129] S2: According to the volume ratio, 1 part of KH-560 was measured and dissolved in 11 parts of ethanol, and 3.5 parts of distilled water were slowly added under stirring, and the pH value was adjusted to 4.5. The mixed solution was allowed to stand for 2.5 hours until the silane coupling agent was fully hydrolyzed to obtain a silane coupling agent solution;

[0130] S3: slowly adding the carbon nanotube solution into the silane coupling agent solution and stirring for 4.5 hours, and obtaining a reaction mixture after the reaction is completed; the mass ratio of the silane coupling agent to the carbon nanotube is 0.4:1.

[0131] S4: baking the reaction mixture, cooling it to room temperature and then vacuum drying it to obtain carbon nanotubes modified with a silane coupling agent.

[0132] S5: Ultrasonic dispersion of carbon nanotubes modified with silane coupling agent in aqueous solution and adding aniline, stirring and mixing thoroughly; ice-cooling and adding ammonium persulfate solution, stirring is continued at 0°C for 4 hours, and after the reaction is completed, polyaniline-coated carbon nanotubes are obtained by filtering, washing and drying; the mass ratio of carbon nanotubes modified with silane coupling agent to aniline is 1:10, and aniline:ammonium persulfate = 1:0.1.

[0133] S6: Add polyaniline-coated carbon nanotubes to an aqueous solution containing 1.1 wt.% sodium dodecylbenzene sulfonate at a mass ratio of 1:500, and obtain a carbon nanotube suspension after ultrasonic treatment; slowly add silica powder to the carbon nanotube suspension, stir evenly, heat to 85°C and continue stirring for 3.5 hours to obtain a composite semi-finished product; the mass ratio of silica to polyaniline-coated carbon nanotubes is 13:1.

[0134] S7: Dry the semi-finished composite material in air, and then heat it to 500±100°C in a tubular furnace at a heating rate of 5±1°C / min for 120 to 160 min. After cooling, the semi-finished composite material is sieved and washed to obtain a finished SiO2-CNTs composite material, i.e., the antistatic agent.

[0135] Oil configuration:

[0136] The preset formula is: by mass, 70 parts of lubricant isooctyl oleate, 53 parts of emulsifier polyglycerol monofatty acid ester, 6 parts of antistatic agent, and 1.5 parts of stabilizer Tween 80.

[0137] The preparation method of the oil agent and the oiling method are the same as those in Example 1.

[0138] Example 3

[0139] Preparation of antistatic agent:

[0140] S1: weighing or measuring 1 part of carbon nanotubes and 110 parts of ethanol by weight, adding the carbon nanotubes into the ethanol and performing ultrasonic dispersion to obtain a carbon nanotube solution;

[0141] S2: According to the volume ratio, 1 part of KH-550 was measured and dissolved in 12 parts of ethanol, and 3 parts of distilled water were slowly added under stirring, and the pH value was adjusted to 5. The mixed solution was allowed to stand for 4 hours until the silane coupling agent was fully hydrolyzed to obtain a silane coupling agent solution;

[0142] S3: slowly adding the carbon nanotube solution into the silane coupling agent solution and stirring for 5 hours, and obtaining a reaction mixture after the reaction is completed; the mass ratio of the silane coupling agent to the carbon nanotube is 0.3:1.

[0143] S4: baking the reaction mixture, cooling it to room temperature and then vacuum drying it to obtain carbon nanotubes modified with a silane coupling agent.

[0144] S5: Ultrasonic dispersion of carbon nanotubes modified with silane coupling agent in aqueous solution and adding aniline, stirring and mixing thoroughly; ice-cooling and adding ammonium persulfate solution, stirring is continued at 0°C for 4.5 hours. After the reaction is completed, polyaniline-coated carbon nanotubes are obtained by filtering, washing and drying; the mass ratio of carbon nanotubes modified with silane coupling agent to aniline is 1:8, and aniline:ammonium persulfate = 1:0.07.

[0145] S6: Add polyaniline-coated carbon nanotubes to an aqueous solution containing 1.2 wt.% sodium dodecylbenzene sulfonate at a mass ratio of 1:480, and obtain a carbon nanotube suspension after ultrasonic treatment; slowly add silica powder to the carbon nanotube suspension, stir evenly, heat to 95°C and continue stirring for 3 hours to obtain a composite semi-finished product; the mass ratio of silica to polyaniline-coated carbon nanotubes is 10:1.

[0146] S7: Dry the semi-finished composite material in air, and then heat it to 500±100°C in a tubular furnace at a heating rate of 5±1°C / min for 120 to 160 min. After cooling, the semi-finished composite material is sieved and washed to obtain a finished SiO2-CNTs composite material, i.e., the antistatic agent.

[0147] Oil configuration:

[0148] The preset formula is: by mass, 65 parts of lubricant isooctyl stearate, 60 parts of emulsifier castor oil polyoxyethylene ether, 8 parts of antistatic agent, and 1.8 parts of stabilizer polyether modified silicone oil.

[0149] The preparation method of the oil agent and the oiling method are the same as those in Example 1.

[0150] Example 4

[0151] Preparation of antistatic agent:

[0152] S1: weigh or measure 1 part of carbon nanotubes and 105 parts of ethanol by weight, add the carbon nanotubes into the ethanol and perform ultrasonic dispersion to obtain a carbon nanotube solution;

[0153] S2: According to the volume ratio, 1 part of KH-560 was measured and dissolved in 10 parts of ethanol, and 3.5 parts of distilled water were slowly added under stirring, and the pH value was adjusted to 4.5. The mixed solution was allowed to stand for 3 hours until the silane coupling agent was fully hydrolyzed to obtain a silane coupling agent solution;

[0154] S3: slowly adding the carbon nanotube solution into the silane coupling agent solution and stirring for 4 hours, and obtaining a reaction mixture after the reaction is completed; the mass ratio of the silane coupling agent to the carbon nanotube is 0.25:1.

[0155] S4: baking the reaction mixture, cooling it to room temperature and then vacuum drying it to obtain carbon nanotubes modified with a silane coupling agent.

[0156] S5: Ultrasonic dispersion of carbon nanotubes modified with silane coupling agent in aqueous solution and adding aniline, stirring and mixing thoroughly; ice-cooling and adding ammonium persulfate solution, stirring is continued at 0°C for 6 hours, and after the reaction is completed, polyaniline-coated carbon nanotubes are obtained by filtering, washing and drying; the mass ratio of carbon nanotubes modified with silane coupling agent to aniline is 1:7, and aniline:ammonium persulfate = 1:0.09.

[0157] S6: Add polyaniline-coated carbon nanotubes into an aqueous solution containing 1 wt.% sodium dodecylbenzene sulfonate at a mass ratio of 1:430, and obtain a carbon nanotube suspension after ultrasonic treatment; slowly add silica powder into the carbon nanotube suspension, stir evenly, heat to 80°C and continue stirring for 3.5 hours to obtain a composite semi-finished product; the mass ratio of silica to polyaniline-coated carbon nanotubes is 15:1.

[0158] S7: Dry the semi-finished composite material in air, and then heat it to 500±100°C in a tubular furnace at a heating rate of 5±1°C / min for 120 to 160 min. After cooling, the semi-finished composite material is sieved and washed to obtain a finished SiO2-CNTs composite material, i.e., the antistatic agent.

[0159] Oil configuration:

[0160] The preset formula is: by mass, 55 parts of smoothing agent glyceryl trioleate, 23 parts of emulsifier cardanol polyoxyethylene ether + 34 parts of polyglycerol monofatty acid ester, 4 parts of antistatic agent, and 2 parts of stabilizer trifluoropropyl methyl silicone oil.

[0161] The preparation method of the oil agent and the oiling method are the same as those in Example 1.

[0162] Comparative Example 1

[0163] Compared with Example 4, the carbon nanotubes were not modified with a silane coupling agent (no steps S2 and S3), and the other process conditions and operations were the same.

[0164] Comparative Example 2

[0165] Compared with Example 4, polyethylene glycol is used instead of polyaniline to coat the carbon nanotubes, and the other process conditions and operations are the same.

[0166] Comparative Example 3

[0167] Compared with Example 4, the process of loading carbon nanotubes with silicon dioxide is omitted (no step S6), and the other process conditions and operations are the same.

[0168] Performance testing:

[0169] Test standards for breaking strength and initial modulus of ultra-high molecular weight polyethylene fiber: refer to GB / T19975-2005 high-strength fiber filament tensile performance test method. Static voltage is measured using Keyence SK-H static meter. High temperature resistance test: put the fiber into a 200℃ oven for 72 hours and then take it out to test its breaking strength. The test results are shown in Table 1;

[0170]

[0171] It can be seen from the above table that in Comparative Example 1, since the carbon nanotubes were not modified with a silane coupling agent, the carbon nanotubes aggregated and piled up, the antistatic performance decreased, the static voltage increased, and the lack of the reinforcing effect of the carbon nanotubes caused the initial modulus and breaking strength to decrease.

[0172] Since comparative example 2 uses polyethylene glycol instead of polyaniline, the synergistic conductive effect of polyaniline and carbon nanotubes cannot be exerted, so the antistatic performance is reduced and the static voltage is increased.

[0173] In Comparative Example 3, since silicon dioxide was omitted as a carrier, polyaniline-coated carbon nanotubes were directly added to the oil. Due to the lack of silicon dioxide, the thermal stability of the fiber decreased, and the breaking strength decreased significantly after high-temperature treatment. At the same time, the dispersion uniformity of the carbon nanotubes decreased, and the carbon nanotubes were easy to settle and aggregate in the oil, resulting in a decrease in the fiber breaking strength.

[0174] In summary, the ultra-high molecular weight polyethylene fiber treated with the oil agent (including the electrostatic agent provided by the present invention) has an electrostatic voltage of ≤0.041 kV, an initial modulus ≥1900 cN / dtex, an initial breaking strength ≥40.0 cN / dtex, and a small decrease in breaking strength under high temperature conditions; the fiber is placed in a 200°C oven for 72 hours and then taken out, and the breaking strength decreases by ≤9.2%.

[0175] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. An oil for ultra-high molecular weight polyethylene fiber, characterized in that: The oil comprises a lubricant, an emulsifier, an antistatic agent and a stabilizer; the antistatic agent is a SiO2-CNTs composite material; Among them, the preparation method of the SiO2-CNTs composite material is: first, carbon nanotubes are modified by using a silane coupling agent, then the modified carbon nanotubes are coated with polyaniline, and finally the polyaniline-coated modified carbon nanotubes are loaded on a silica carrier to obtain a finished SiO2-CNTs composite material, namely the antistatic agent.

2. The oil according to claim 1, characterized in that The components of the oil agent are as follows by mass: 50 to 70 parts of a smoothing agent, 50 to 60 parts of an emulsifier, 4 to 8 parts of an antistatic agent, and 1 to 2 parts of a stabilizer.

3. The oil according to claim 1, characterized in that The lubricant is one or more of lauryl oleate, isooctyl oleate, isooctyl stearate, triolein, and mineral oil.

4. The oil according to claim 1, characterized in that The emulsifier is one or more of cardanol polyoxyethylene ether, polyglycerol monofatty acid ester, and castor oil polyoxyethylene ether.

5. The oil according to claim 1, characterized in that The stabilizer is one or more of acrylic acid polyether silicone oil, Tween 80, polyether modified silicone oil, and trifluoropropyl methyl silicone oil.

6. The oil according to claim 1, characterized in that The ultra-high molecular weight polyethylene fiber treated with the oil has an electrostatic voltage of ≤0.041 kV, an initial modulus of ≥1900 cN / dtex, an initial breaking strength of ≥40.0 cN / dtex, and the fiber is placed in a 200° C. oven for 72 hours and then taken out, and the breaking strength decreases by ≤9.2%.

7. A method for preparing the oil according to any one of claims 1 to 6, characterized in that: The specific steps include: S21: weigh the raw materials according to the preset formula, put the smoothing agent and the emulsifier into a stirring tank, and stir them evenly at room temperature; S22: While continuing to stir, slowly add the antistatic agent to ensure that the antistatic agent is evenly dispersed throughout the mixture; S23: Add stabilizer to the mixture and continue stirring for more than 30 minutes to ensure that all ingredients are fully blended to obtain a semi-finished oil preparation; S24: adjusting the pH value and viscosity of the semi-finished oil, filtering and filling into a storage container, i.e., the finished oil.

8. The preparation method according to claim 7, characterized in that: The pH value range is 6-7, and the viscosity range is 100mPa·s-115mPa·s; the pH regulator used is potassium hydroxide or triethanolamine.

9. A method for using the oil according to any one of claims 1 to 6, characterized in that: The specific steps include: S31: preparing an ultra-high molecular weight polyethylene high viscosity solution; S32: Extruding the high viscosity solution through a spinning nozzle with a spinneret aperture of 1 mm and an aspect ratio of 6 to 12 to form filaments at a spinning temperature of 250° C. to 280° C. to obtain ultra-high molecular weight polyethylene fibers; S33: After the initial cooling, the fiber is immediately sent to the stretching machine for heat stretching; the stretching temperature is set at 120℃~140℃, and the stretching ratio is 5~10 times of the original length; S34: The stretched fiber is oiled by a coating device, cooled and dried after oiling, and then rolled up on a reel to obtain a finished fiber product.

Citation Information

Patent Citations

  • Low-thermal-conductivity carbon nanotube composite material and preparation method thereof

    CN106188536A

  • Preparative method of conductive silica nano-tube composite by using in situ polymerization of aniline

    KR1020100008934A